Role of Endothelial and Mesenchymal Cell Transitions in Heart Failure and Recovery Thereafter - Wang, Guangyu; Cruz, Ana Sofia; Youker, Keith; Marcos-Abdala, Hernan G.; Thandavarayan, Rajarajan A.; Cooke, John P.; Torre-Amione, Guillermo; Chen, Kaifu; Bhimaraj, Arvind (Frontiers in Genetics, 2021)
Background: Mechanisms of myocardial recovery are not well elucidated. Methods: 3-month-old C57/BL6 mice were treated with Angiotensin-II infusion and N (w)-nitro-L-arginine methyl ester in drinking water to induce HF at 5 weeks. These agents were discontinued, and animals studied with echocardiographic, histological and genetic assessment every 2 weeks until week 19. mRNA was extracted from these samples and human pre-post LVAD samples. Results: Histologic and echo characteristics showed progressive worsening of cardiac function by week 5 and normalization by week 19 accompanied by normalization of the transcriptional profile. Expression of 1350 genes were upregulated and 3050 genes down regulated in HF compared to controls; during recovery, this altered gene expression was largely reversed. We focused on genes whose expression was altered during HF but reverted to control levels by Week 19. A gene ontology (GO) analysis of this cohort of genes implicated pathways involved in EMT and MET. The cohort of genes that were differentially regulated in heart failure recovery in the murine model, were similarly regulated in human myocardial samples obtained pre- and post-placement of a left ventricular assist device (LVAD). Human end stage HF myocardial samples showed cells with dual expressed VE-Cadherin and FSP-1 consistent with cell fate transition. Furthermore, we observed a reduction in fibrosis, and an increase in endothelial cell density, in myocardial samples pre- and post-LVAD. Conclusions: Cell fate transitions between endothelial and mesenchymal types contribute to the pathophysiology of heart failure followed by recovery. Key words: Heart failure, Cardiac recovery, Endothelial to mesenchymal transition, Mesenchymal to endothelial transition, Gene expression.